Some morphological and word-building features of imitative words - Mazhitayeva, S.M.; Saparova, K.O.; Abduyov, M.I.; Khamzina, G.S.; Nygmetova, N.T.; Zhetpisbay, S.A. (Marsland Press / Zhengzhou University, 2014)
Imitative words are language phenomenon that traces back to early times. As any other words they had been improving through the process of language development thanks to folk literatures and every day speech. However, the division of imitative as a separate part of Speech still has not found its solution. There are some actual problems that can be solved. They are: two types of imitative words: words, reproducing or representing a natural sound and words, representing a manner or image, their lexical and semantic features, communicative-pragmatic characteristics, their derivations; general study of imitative words in the Turk and Kazakh linguistics; morphological, semantic, syntactic peculiarities; capacities to build new words, a role in a sentence, the ways to combine with other members of the sentence.
Keywords: word-building; word-formation; ancient Turkic language; comparative-historical researches; imitative (imitative) words